Performativitas Muslimah Style sebagai Strategi Dramaturgi Mahasiswi dalam Pencarian Social-Esteem di Media Sosial - Rhifand, Nasywa Nabila (Jayapangus Press, 2026)
This research analyzes the performativity of muslimah style as a dramaturgical strategy applied by muslim female students in gaining social-esteem on social media. The research uses a qualitative approach with a dramaturgical perspective to understand how muslimah identity is displayed and managed in digital space. Data was obtained through in-depth interviews with eight muslimah students from various universities in Indonesia who are active in uploading muslimah style content on social media and represented in the digital space, accompanied by observation of the informants digital content. The results show that performativity of muslimah style is not only an expression of religious identity, but also a conscious strategy for managing impressions through front stage and back stage practices. Female students consciously curate visual displays, captions, and interactions with audiences to build an image of muslim women who are both religious and stylish. Digital feedback such as likes, comments, and the number of followers serve as a form of social evaluation that contributes to the formation of social esteem. These findings indicate that the performativity of muslimah style practice in the digital space is a strategic and complex managed performance, as well as an adaptive response to pressure from the fashion market, religious norms, and the logic of digital platforms.